2020
DOI: 10.1016/j.ssmph.2019.100472
|View full text |Cite|
|
Sign up to set email alerts
|

The socio-economic distribution of exposure to Ebola: Survey evidence from Liberia and Sierra Leone

Abstract: Socio-economic factors are widely believed to have been an important driver of the transmission of Ebola Virus Disease (EVD) during the West African outbreak of 2014–16, however, studies that have investigated the relationship between socio-economic status (SES) and EVD have found inconsistent results. Using nationally representative household survey data on whether respondents knew a close friend or family member with Ebola, we explore the SES determinants of EVD exposure along individual, household, and comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Still, some results are worth mentioning about these demographic indicators. Young adults (ages between [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] and adults (ages between 34-50) constituted 77% of the investigated sample, but they constitute 86% of the respondents at risk. Also, 50% of the study respondents have an agriculture-related occupation but when computing the percentage within respondents at risk we obtained 79%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Still, some results are worth mentioning about these demographic indicators. Young adults (ages between [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] and adults (ages between 34-50) constituted 77% of the investigated sample, but they constitute 86% of the respondents at risk. Also, 50% of the study respondents have an agriculture-related occupation but when computing the percentage within respondents at risk we obtained 79%.…”
Section: Discussionmentioning
confidence: 99%
“…In that context, it has been shown that, typically, people with lower socioeconomic status have higher exposure to risk factors than the wealthier segments of the population [28]. While a consensus on the relationship between SDE factors and exposure to infectious diseases has not been reached [29], some modeling studies support the idea that poverty has an effect on the spread of infectious diseases [30][31][32]. However, we point out that this relationship is mostly supported by aggregate data at the country level (e.g., GDP) and not for individuals.…”
Section: Introductionmentioning
confidence: 99%
“…It is argued that growing inequality leads to deteriorating health conditions for the poor and increased exposure to foreign germs by the increasingly more mobile rich (Kohn, 2007; Turchin, 2007). The relevance of these historic studies has been raised in the context of the COVID‐19 case (see Spinney, 2020; Turchin, 2020), and the role of social factors has been demonstrated for other global diseases, such as Ebola (Grepin et al, 2020). Thus, historic or path‐dependent inequality is likely to be associated with the uneven spread of COVID‐19.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In that context, it has been shown that, typically, people with lower socioeconomic status have higher exposure to risk factors than the wealthier segments of the population [28]. While a consensus on the relationship between SDE factors and exposure to infectious diseases has not been reached [29], some modeling studies support the idea that poverty has an effect on the spread of infectious diseases [30][31][32]. However, we point out that this relationship is mostly supported by aggregate data at the country level (e.g., GDP) and not at the individual level.…”
Section: Introductionmentioning
confidence: 99%